Peran Lingkungan Sekolah Terhadap Motivasi Belajar Siswa Kelas X di SMA Muhammadiyah Maumere - Andreas Afriyanto Moa; Fitriah Fitriah; Mariana Sada (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to determine the extent of the role of the school environment in influencing the learning motivation of class X students in Muhammadiyah Maumere High School. The school environment is an external factor that plays an important role in supporting or inhibiting the learning process of students. The factors studied in this study include the physical condition of the school (such as classrooms, libraries, laboratories, and sports facilities), social aspects (support of teachers and peers), as well as psychological aspects (comfort, appreciation, and conducive learning atmosphere). The method used in this study is a qualitative descriptive method with data collection techniques through observation, interviews, and questionnaires to students and teachers. The result of the study shows that school facilities in Muhammadiyah Maumere High School still have many limitations, including inadequate classrooms, lack of learning technology tools such as projectors, small libraries with limited collection of books, and the unavailability of special space for arts and special sport facilities. However, despite these limitations, most students still show a high level of learning motivation. This is influenced by the support of teachers and peers, involvement in extracurricular activities, family support, and personal expectations of student achievement. This study concluded that the school environment indeed plays an important role in shaping student learning motivation, but social and psychological factors also have a big influence. Therefore, it is recommended that schools make improvements and develop physical facilities and strengthen positive social climate to support the student learning process optimally.